2018
DOI: 10.5194/essd-10-2069-2018
|View full text |Cite
|
Sign up to set email alerts
|

The Berkeley High Resolution Tropospheric NO<sub>2</sub> product

Abstract: Abstract. We describe upgrades to the Berkeley High Resolution (BEHR) NO2 satellite retrieval product. BEHR v3.0B builds on the NASA version 3 standard Ozone Monitoring Instrument (OMI) tropospheric NO2 product to provide a high spatial resolution product for a domain covering the continental United States and lower Canada that is consistent with daily variations in the 12 km a priori NO2 profiles. Other improvements to the BEHR v3.0 product include surface reflectance and elevation, and factors affecting the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 95 publications
2
67
1
Order By: Relevance
“…Data availability. All datasets are publicly available online: GeoTASO data are archived at https://www-air.larc.nasa.gov/ cgi-bin/ArcView/lmos (Janz et al, 2019), Pandora NO 2 data are found at http://judd2019.pandonia-global-network.org/ (last access: 4 November 2019) and produced following https://www.pandonia-global-network.org/wp-content/uploads/ 2019/11/BlickSoftwareSuite_Manual_v1-7.pdf (LuftBlick, 2017), and OMI data are from Laughner et al (2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data availability. All datasets are publicly available online: GeoTASO data are archived at https://www-air.larc.nasa.gov/ cgi-bin/ArcView/lmos (Janz et al, 2019), Pandora NO 2 data are found at http://judd2019.pandonia-global-network.org/ (last access: 4 November 2019) and produced following https://www.pandonia-global-network.org/wp-content/uploads/ 2019/11/BlickSoftwareSuite_Manual_v1-7.pdf (LuftBlick, 2017), and OMI data are from Laughner et al (2018b).…”
Section: Discussionmentioning
confidence: 99%
“…OMI is a space-based UV-VIS instrument launched in 2004 aboard the EOS-Aura satellite in a sun-synchronous orbit with an Equator crossing time in the early afternoon (Levelt et al, 2006). This work uses the NASA standard product (SP) version 3 and the Berkeley High Resolution (BEHR) product (Russell et al, 2011;Laughner et al, 2018bLaughner et al, , 2019 to assess how their tropospheric column retrievals compare with measurements from Pandora spectrometers deployed during summer 2017 in the LMOS and the LA Basin domains. The two vertical column products are based on the same slant columns (produced by the SP retrieval), but they differ in their a priori inputs for the tropospheric air mass factor calculation.…”
Section: Ozone Monitoring Instrument (Omi)mentioning
confidence: 99%
“…Celarier et al, 2008;Kramer et al, 2008;Chen et al, 2009;Irie et al, 2012;Ma et al, 2013;Wu et al, 2013;Kanaya et al, 2014;Wang et al, 2017;Drosoglou et al, 2017Drosoglou et al, , 2018. Other possible explanations include the uncertainties in the applied satellite retrieval assumptions, such as the choices of surface albedo, a priori NO 2 profiles, or cloud and aerosol treatment (Boersma et al, 2004Leitão et al, 2010;Heckel et al, 2011;Lin et al, 2014Lin et al, , 2015. The best agreement is generally obtained in the case of suburban and remote stations, but difficulties may arise when small local sources are present in a remote location, such as Réu-nion island or Bujumbura Gielen et al, 2017).…”
Section: Uncertainty Estimates For Gome-2 Total and Tropospheric Nomentioning
confidence: 99%
“…This trend matches satellite observations of NO 2 over the continental United States. Figure 8 shows the cumulative frequency distribution of summertime tropospheric NO 2 columns from 2005-2007 and 2015-2017 using the BErkeley High-Resolution (BEHR) v3.0A retrieval (Laughner et al, 2018a) of slantcolumn measurements from ozone monitoring instrument (OMI). Over this time, the highest percentiles of NO 2 concentrations have decreased and the lowest percentiles increased, leading to a significantly narrower distribution of NO 2 concentrations.…”
Section: Impacts Of the Transition From The Hno 3 To The Rono 2 Regimementioning
confidence: 99%